(3TQM GdThGgO GdcHQis - (3eMehO Hf CMeO Hf ehSi Hf CMeO, CHh eMeO, HOQ GdOjf GdYjfj , J (B855 (3g` s; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s
(3ChdgG (B:s
(3hHYO deG QCjJ TOI EgJeGe eMUdj GdfMh aj GdeOGQc, hZGjI CdaJge HcJGH CdajI GHf eGdc s
(3BNQgG (B:s
(3GdEYQGH(B: (3bhdg(B: (3CdjJ LedI ef GdaYd hGdaGYd bhdg(B: (3MH GdYQGb cdGe EVGaj efUhH HfRY GdNGaV s
(3CdajI GHf eGdc GdeSeGI HGdNdGUIs
(3fSNI KGfjIs
(3JJab aj ChdgG eY GdfSNI GdChdi HGNJdGa jSjQ LOkG aj HYV GdCdaGXs
(3hHChdgG JQLeI ddeDda ef cJGH MSf GdeMGVQI dLdGd GdSjhWj s
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdfMhs